2020
DOI: 10.1002/14651858.cd013513.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Biologics for chronic rhinosinusitis

Abstract: Biologics for chronic rhinosinusitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 93 publications
0
26
0
2
Order By: Relevance
“…In a recent Coch­rane review evaluating nasal irrigation for allergic rhinitis, the researchers performed a subgroup analysis for the type of irrigation device. However, there was heterogeneity among the studies that were reviewed, and the results were inconclusive [3, 13, 14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent Coch­rane review evaluating nasal irrigation for allergic rhinitis, the researchers performed a subgroup analysis for the type of irrigation device. However, there was heterogeneity among the studies that were reviewed, and the results were inconclusive [3, 13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…Nasal saline irrigation is a common procedure to relieve nasal symptoms in upper respiratory tract infection such as nasopharyngitis (common cold) and rhinosinusitis [1-3]. The physician usually prescribes normal saline along with the appropriate medications (e.g., antihistamines, nasal steroids, or antibiotics) to treat these conditions [1, 4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…In Chong’s systematic review and meta-analysis, there were three small studies with 65 participants (Gavaert 2013, Pinto 2010 and NCT01066104) evaluated omalizumab. 13 Their results also showed that there were very uncertain about the effect of omalizumab on disease-specific HRQoL, SAEs, the extent of disease (CT scan scores), generic HRQoL and adverse effects. NCT01066104 19 included in Chong’s review was unpublished data, so it was excluded in our study according to our inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…But they found very little information or insufficient evidence about the use of omalizumab and cannot determine whether it was effective or not. 12 13 Currently, some well-designed RCTs about omalizumab for CRSwNP were published, 14 Open access provide us with some evidence. Therefore, this systematic review was conducted to evaluate the efficacy and safety of omalizumab vs placebo in adult patients with CRSwNP, and identify evidence gaps that will guide future research on omalizumab for CRSwNP.…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of currently prescribed pharmaceutical agents bear either the OCF 3 or OCF 2 H motif in their aromatic systems, for example Sonidegib® (anticancer drug), Riluzole® (anticonvulsant drug) Pantoprazole® (anti‐inflammatory drug), and Roflumilast® (anti‐inflammatory drug; Figure b), access to these analogues often requires installation of the OCF 3 and OCF 2 H groups at an early stage of a multistep synthetic sequence . The lack of late‐stage tri‐ and difluoromethoxylation strategies results in laborious synthetic efforts for the preparation of a handful of structurally related analogues and limits the number of derivatives for structure–activity relationship studies .…”
Section: Introductionmentioning
confidence: 99%